#TITLE_ALTERNATIVE# - DWIPUTRA ( NIM :1530910 ), DANIEL
Municipal solid waste management in Bandung, West Java, is hampered by the lack of garbage trucks. In order to solve this problem, increasing the density of waste by using compaction method is necessary so that more waste can be fitted in garbage trucks, resulting in a more efficient garbage transportation. However, compaction method also brings potential problems, namely leachate as a side product of waste compaction which can not be dumped offhandedly before treated properly. Thus, a leachate treatment plant was built in order to overcome the problem. The leachate treatment plant consists of series of biological, physical, and chemical treatment method designed to reduce toxic substances in leachate so that it can be dumped safely into bodies of water. The biological treatment method itself contains series of anaerobic and aerobic process, while the physical and chemical treatment method contains series of coagulation-flocculation and filtration proccess. Based on the research results, Tegalega LTP’s processing unit consists of a biological treatment unit with anaerobic and aerobic process, each of them capable of removing COD to 47%, coagulation-flocculation unit with COD removal efficiency of 46% and TSS removal of 71% for a PAC dose of 3.6 g/l, and a filtration unit with COD removal efficiency of 63% and TSS of 79% for the discharge of 0.25 l/min. Research done suggests that Tegalega LTP has a potential of removing a total amount of 94% of COD and 95% of TSS. However, analysis of operational conditions in the field showed many shortcomings in terms of equipment and human resources so that the operation of leachate treatment didn’t reach its maximum potential.